2012
DOI: 10.1542/peds.2011-3326
|View full text |Cite
|
Sign up to set email alerts
|

Improving Notification of Sexually Transmitted Infections: A Quality Improvement Project and Planned Experiment

Abstract: BACKGROUND AND OBJECTIVE: Inadequate follow-up of positive sexually transmitted infection (STI) test results is a gap in health care quality that contributes to the epidemic of STIs in adolescent women. The goal of this study was to improve our ability to contact adolescent women with positive STI test results after an emergency department visit. METHODS:We conducted an interventional quality improvement project at a pediatric emergency department. Phase 1 included plando-study-act cycles to test interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…The prevalence of STIs in this population is high: 8% have NG and 15% have TV 15. Because of the high volume and high prevalence in the ED, we implemented a quality improvement (QI) project to improve follow-up care for adolescent women diagnosed with an STI.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of STIs in this population is high: 8% have NG and 15% have TV 15. Because of the high volume and high prevalence in the ED, we implemented a quality improvement (QI) project to improve follow-up care for adolescent women diagnosed with an STI.…”
Section: Introductionmentioning
confidence: 99%
“…5,13 Recently, we showed that we can improve our ability to contact women with their STI test results, and reduced our lost to follow-up rate from 40% to 24%. 3 Thus, timely followup of positive STI results is a necessary public health intervention for adolescent women utilizing the ED.…”
Section: Discussionmentioning
confidence: 99%
“…3 This data was obtained in a busy, urban ED with a high volume of adolescent visits and a high prevalence of STIs. We identified a cohort of all female patients ages 14-21 who were tested for STIs in the ED between January and October 2009.…”
Section: Study Design Setting and Populationmentioning
confidence: 99%
See 2 more Smart Citations